Complex robotic compared to manual coronary interventions: 6‐ and 12‐month outcomes. Issue 4 (19th November 2018) - Walters, Daniel; Reeves, Ryan R.; Patel, Mitul; Naghi, Jesse; Ang, Lawrence; Mahmud, Ehtisham
Abstract: Objectives: To assess the long‐term safety and efficacy of robotic percutaneous coronary revascularization for use in complex coronary lesions. Background: Robotically assisted percutaneous coronary intervention (PCI) is safe and feasible in simple coronary lesions and has excellent short‐term procedural and clinical outcomes for complex lesions; however, long‐term safety and efficacy outcomes are unknown. Methods: A total of 103 consecutive patients underwent a total of 108 robotic (R)‐PCI procedures (age 68.1; 78.3% male) over 18 months, and 210 patients underwent a total of 226 manual (M)‐PCI procedures (age 67.5; 78.1% male) during the same period. Patients were subsequently followed and both 6‐month and 12‐month major adverse cardiovascular events (MACE), comprised of any death, stroke, myocardial infarction, or target vessel revascularization, are reported and compared. Results: There was no difference between the two groups with regard to overall MACE at 6 months (R‐PCI 5.8% vs. M‐PCI 3.3%, P  = 0.51) or at 12 months (R‐PCI 7.8% vs. M‐PCI 8.1%, P  = 0.92). There was no difference between the individual components of the primary combined endpoint at either time point. No access site complications occurred in either cohort that met BARC III or higher criteria. Conclusions: At the 6‐ and 12‐month time points following R‐PCI, no difference in clinical outcomes or safety measures was observed as compared to M‐PCI.